PERBAIKAN IKLIM BERINVESTASI UNTUK MENINGKATKAN ARUS MASUK NET PENANAMAN MODAL - Silalahi, Donalson (UNIKA Santo Thomas, 2010)
From the time that the crisis of economy at the year 1997, the ï¬‚ows of the net capital investment in Indonesia is low or negative for some period. Thus, the Government is difficulty to realized the target of economic growth at the year 2010. The capital investment is the decisive factor that influence economic growth to compare with the other ï¬actors. Thus, the capital investment is the important facctor to achieved the target of economic growth. The role of the capital investment is difficulty to create if the problems of the climate if the capital investment like that bureaucracy, grease money, and the implementation of autonomy area did not to solve immediately. This paper aims to describes and discuss how to improve the climate of the capital investment to increased the flows of the net capital investment. If the climate of the capital investment in Indonesia to improve, so the ï¬‚ows of the net capital investment is increase and then the economic growth increase too. By the way, the government and the local goverment necessary to improve the climate of the capital investment with implementation of the policy with to give lots of the facilities, ease to investment, and the incentives to investor with mapping the industry if Indonesia.